Investigating Effects of Globalization on Agribusiness in Benue State, Nigeria: A case study of Agro-allied firms - Okpeke, G. A.; Okpachu, O.G.; Adejo, A. M (ADAN JOURNAL OF AGRICULTURE, 2026)
This study investigates the effects of globalization on agro‑allied firms in remote communities of Benue State, Nigeria, using a sample size of 133 small‑scale enterprises (rice millers 42.9 %, cassava/grain grinders 30.8 %, timber sawyers 26.3 %). Most firms (55.6 %) employ 1–5 workers. Approximately 70 % reported tariff reductions on imported agricultural products, 26.3 % had formal trade agreements, and 24.8 % engaged in foreign partnerships. Technological transfer was reported by 69.9 % of firms, and 63.9 % adopted foreign machinery/technologies. Linear regression analysis revealed that trade liberalization (β = 0.471, p value; 0.001), global market trends (β = 0.195, p = 0.025), and hiring foreign workers (β = 0.610, p value; 0.001) significantly enhance productivity. However, globalization variables showed no significant impact on profitability or competitiveness. The study concludes that while globalization improves productivity in remote agro‑allied firms, structural constraints limit broader performance gains. The study recommends the Strengthen of rural infrastructure (roads, electricity, and digital connectivity) to lower transaction costs and improve market access for agro‑allied firms. It recommends targeted financial incentives (low‑interest credit, matching grants) and institutional support to facilitate adoption of foreign machinery and technology transfer.